FACTORS AFFECTING INCREASING MARKETING EFFICIENCY AND DIRECTIONS FOR THEIR EFFECTIVE USE - Tojimatov Izzatbek Ikromali o‘g‘li (Scholars Digest Publishing, 2024)
This article analyzes the factors influencing the increase of marketing efficiency and the directions of their effective use. Digital technologies and their level of impact on customers' outlook were analyzed as factors influencing marketing activities. The impact of the change in the worldview of customers, their level of use of digital applications on marketing activities is discussed. The importance of increasing marketing efficiency, digital technology-based, AI and sensor technologies in marketing activities is highlighted.
Keywords: marketing effectiveness, marketing technologies, digital technologies, optimized content potential, 1 person segmentation, AI and sensor technologies.